Compreendendo as diferenças de gênero a partir de interações livres no contexto escolar - MENEZES, Aline Beckmann de Castro (2011)
Evolutionary Psychology considers that gender differences in play are a result of cultural influences upon pre-dispositions selected in the species. The compatibility of these differences with theoretical prevision was investigated. Seventy three six/seven years old students of private schools were recorded in four 30 minutes sessions. Playful behavior frequency and playmate choice were counted. Later, 21 children were asked about favourite plays and how they classified those plays accordingly to gender patterns. Both sexes participated in similar activities but their interactions were mostly restricted to members of the same sex. It was also observed that there were topographic differences in the way they played, accordingly to sex. The interviews, as shown in the literature, allowed to identify that the speech and the behavior observed were different, with a higher cultural influence upon the speech.